Faktor Internal Dan Ekternal yang Mempengaruhi Permintaan Sukuk Negara Ritel - Gusniarti, Gusniarti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
This study aims to analyze what factors can influence the demand for retail state sukuk. This study uses multiple regression analysis. The research data used is the SR004-007 Retail Sukuk as the dependent variable. The independent variable used is the variable rate of return, price, exchange rate (US dollar exchange rate), inflation, and deposit rates. The results obtained indicate that the variable US dollar exchange rate and deposit rates have an influence on demand for sukuk and yields, prices, and inflation have no effect on demand for retail state sukuk. Based on these results, it shows that retail sukuk yields, retail sukuk prices and inflation in the study period did not affect investors in making decisions to invest in retail state sukuk. While the increase in the US dollar exchange rate caused by the economic slowdown in the study period and deposit interest rates that compete closely with the returns on retail sukuk can influence investors in making decisions to invest in retail state sukuk.